Determination of Engineering Properties of Cactus Pear (Opuntia) (International Journal of Innovative Research in Engineering & Management, 2022)
Wild cactus pears (Opuntia spp.) were  collected from five locations on Turkey's southeastern coast, in the Mediterranean region. The fruit and seed  characteristics were hugely affected by the site.  Colletotrichum species of fungi produce anthracnose,  particularly harms cactus pears in particular. A wet light  brown rot with light pink, spore-producing pustules on the  surface is a sign of infection. Cactus pears available in a  multitude of tastes, textures, and colours, with some of  them proving beneficial to health and used in drug and  cosmetic items. The measurement of engineering  properties of cactus fruit can be beneficial for designing  various processing and harvesting equipment, product  development, food quality control, and food processing Cactus (Opuntia) has stood commercially exploited for  example medicinal, energy, fruit, vegetable, forage besides dye yielding crop cutting-edge the dry besides half-dry parts of the world. This study focus on engineering  properties and textural property of Cactus pear fruit  namely length, width, thickness, equivalent diameter,  weight, sphericity, volume, density, and firmness, ripeness of Cactus pear were observed/determined, which can be  useful for the further processing of cactus pear.
Keywords: Cactus Pear; Cactus Fruits; Engineering Properties; Food; Plant; Water